The organization of internal control at the enterprise: the new purposes and problems (Путеводитель предпринимателя, 2020)
This article discusses the new functionality of the internal control of itsinformation base, in accordance with the operation and the number of new concepts on the control efficiency of business operations, enterprise related to the increase in value-added business.